2022
DOI: 10.1039/d2ra01575g
|View full text |Cite
|
Sign up to set email alerts
|

Cryostorage of unstable N-acetylglucosaminyltransferase-V by synthetic zwitterions

Abstract: We report biocompatible materials for cryostorage of unstable proteins such as cancer-related enzyme, N-acetylglucosaminyltransferase-V (GnT-V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…34,35 Many reports have been published on other proteins as well. 2,34,35,[42][43][44][45][46][47][48] This current review is focused on living organisms, in particular, cells, which are the smallest units of living organisms, and higher organisms. First, the toxicity of [C 8 mim] +based ionic liquids (mentioned in the introduction) is reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Many reports have been published on other proteins as well. 2,34,35,[42][43][44][45][46][47][48] This current review is focused on living organisms, in particular, cells, which are the smallest units of living organisms, and higher organisms. First, the toxicity of [C 8 mim] +based ionic liquids (mentioned in the introduction) is reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In a previous study, we showed that a dilute aqueous OE 2 imC 3 C solution up to 10 wt % can be used to freeze Nacetylglucosaminyltransferase-V (GnT-V), which is an enzyme branching asparagine-linked glycosylation, involved in the aggravation of cancer, and can be used as a cryopreservation medium for deep freezing. 19 The activity of GnT-V in 10 wt % OE 2 imC 3 C solution after cryopreservation was found to be higher than that of a sample stored in an aqueous glycerol solution (20 vol %), which is a commonly used CPA. Furthermore, the percentage of residual GnT-V protein after freezing was also slightly higher in the 10 wt % OE 2 imC 3 C solution than that in the 20 vol % glycerol solution, suggesting that the OE 2 imC 3 C solution prevents the degradation or aggregation of GnT-V during cryopreservation.…”
Section: ■ Introductionmentioning
confidence: 90%
“…In a previous study, we showed that a dilute aqueous OE 2 imC 3 C solution up to 10 wt % can be used to freeze N -acetylglucosaminyltransferase-V (GnT-V), which is an enzyme branching asparagine-linked glycosylation, involved in the aggravation of cancer, and can be used as a cryopreservation medium for deep freezing . The activity of GnT-V in 10 wt % OE 2 imC 3 C solution after cryopreservation was found to be higher than that of a sample stored in an aqueous glycerol solution (20 vol %), which is a commonly used CPA.…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed zwitterions, including OE 2 imC 3 C (Figure ), as novel cryoprotectants. Zwitterions are not permeable to cells and do not affect the cytoplasm, which results in low cytotoxicity, and zwitterions strongly inhibit ice crystallization. , Therefore, a zwitterion aqueous solution can efficiently cryopreserve various cells . However, this did not work for some cell lines.…”
Section: Introductionmentioning
confidence: 99%